PROS AND CONS OF TED-BASED LISTENING INSTRUCTION FOR ENGLISH MAJORS IN CHINA: STUDENTS’ INSIGHTS - Huang Jian (University of Kuningan, 2015)
Listening is essential not only for successful communication of various kinds but also for effective language acquisition (Rivers, 1981; Wang, 2012). Unfortunately, in spite of its significance, listening instruction and relevant research has been downplayed because of difficulty of teaching listening and a wrong belief that listening competence can be acquired simply through exposure (Ren, 2011; Field, 2008). The limited research into the instruction has revealed that listening instruction follows the comprehension approach (CA) which reduces listening teaching to listening testing Brown, 1990, Vandergrift Goh, 2012. As a result, listening leaners often fail to receive instruction on how to listen and gradually lose their motivation for listening learning. The study aims to change this situation by using Ted-based materials for listening instruction. Via both quantitative and qualitative analysis of the data collected, the study shows that Ted-based listening instruction helps students’ all-around development in terms of language proficiency, critical thinking (CT), world knowledge and affects though improvement are desired in choice of text in terms of right difficulty, length and speaker features.Keywords: Listening instruction, material development, ted, student perspective.